miRNApath: A database of miRNAs, target genes and metabolic pathways - Chiromatzo, A. O.; Oliveira, T. Y. K.; Pereira, G.; Costa, A. Y.; Montesco, C. A. E.; Gras, D. E.; Yosetake, F.; Vilar, J. B.; Cervato, M.; Prado, P. R. R.; Cardenas, R. G. C. C. L.; Cerri, R. [UNESP]; et al. (My University, 2007)
MicroRNAs (miRNAs) are small non-coding RNAs that regulate target gene expression and hence play important roles in metabolic pathways. Recent studies have evidenced the interrelation of miRNAs with cell proliferation, differentiation, development, and diseases. Since they are involved in gene regulation, they are intrinsically related to metabolic pathways. This leads to questions that are particularly interesting for investigating medical and laboratorial applications. We developed an miRNApath online database that uses miRNA target genes to link miRNAs to metabolic pathways. Currently, databases about miRNA target genes (DIANA miRGen), genomic maps (miRNAMap) and sequences (miRBase) do not provide such correlations. Additionally, miRNApath offers five search services and a download area. For each search, there is a specific type of input, which can be a list of target genes, miRNAs, or metabolic pathways, which results in different views, depending upon the input data, concerning relationships between the target genes, miRNAs and metabolic pathways. There are also internal links that lead to a deeper analysis and cross-links to other databases with more detailed information. miRNApath is being continually updated and is available at http://lgmb.fmrp.usp.br/mirnapath. ©FUNPEC-RP.
Keywords: Database; Interaction; Investigation; Metabolic pathways; MicroRNA; Target genes; microRNA; RNA; cell differentiation; cell maturation; cell proliferation; conference paper; correlation analysis; cross linking; gene control; gene expression; gene sequence; genomics; laboratory; metabolism; Animals; Computational Biology; Databases, Nucleic Acid; Humans; Metabolic Networks and Pathways; MicroRNAs; Software